2020
DOI: 10.1126/sciadv.abc0367
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 represses a neonatal/reparative gene program in adult intestinal epithelium

Abstract: Intestinal epithelial homeostasis is maintained by adult intestinal stem cells, which, alongside Paneth cells, appear after birth in the neonatal period. We aimed to identify regulators of neonatal intestinal epithelial development by testing a small library of epigenetic modifier inhibitors in Paneth cell–skewed organoid cultures. We found that lysine-specific demethylase 1A (Kdm1a/Lsd1) is absolutely required for Paneth cell differentiation. Lsd1-deficient crypts, devoid of Paneth cells, are still able to fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 55 publications
(104 reference statements)
6
26
0
Order By: Relevance
“…This pattern change was even more pronounced in SI crypt IECs from Villin -Cre+ Lsd1 f/f mice, which conditionally lack Lsd1 in IECs, compared to wild type (WT) littermates ( Figure 4D ). Similar gating has previously been associated with enteroendocrine cells and their progenitors (Sato et al, 2011 ), which thus fits with our previous observation that enteroendocrine progenitors such as Neurod1 and Neurog3 are upregulated in Villin -Cre+ Lsd1 f/f mice (Zwiggelaar et al, 2020 ). However, upon performing intracellular flow cytometry staining for the canonical tuft cell marker DCLK1, we found that also a DCLK1 hi population fell within this gate and is increased in Lsd1 -deficient crypts ( Figure 4E ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This pattern change was even more pronounced in SI crypt IECs from Villin -Cre+ Lsd1 f/f mice, which conditionally lack Lsd1 in IECs, compared to wild type (WT) littermates ( Figure 4D ). Similar gating has previously been associated with enteroendocrine cells and their progenitors (Sato et al, 2011 ), which thus fits with our previous observation that enteroendocrine progenitors such as Neurod1 and Neurog3 are upregulated in Villin -Cre+ Lsd1 f/f mice (Zwiggelaar et al, 2020 ). However, upon performing intracellular flow cytometry staining for the canonical tuft cell marker DCLK1, we found that also a DCLK1 hi population fell within this gate and is increased in Lsd1 -deficient crypts ( Figure 4E ).…”
Section: Resultssupporting
confidence: 92%
“…Treatment with GSK-LSD1 markedly reduced gene expression of Paneth and goblet cell markers, but caused an increase in enteroendocrine and tuft cell marker genes, particularly Gfi1b ( Figure 4B ). This supports our recent work in which we found that Lysine-specific Demethylase 1A (LSD1, KDM1A) is required for Paneth cell differentiation and contributes to goblet cell differentiation (Parmar et al, 2020 ; Zwiggelaar et al, 2020 ). Paneth cells are commonly gated as SSC hi CD24+ population in flow cytometry (Sato et al, 2011 ).…”
Section: Resultssupporting
confidence: 91%
“…4d ). Similar gating has previously been associated with enteroendocrine cells and their progenitors 26 , which thus fits with our previous observation that enteroendocrine progenitors such as Neurod1 and Neurog3 are upregulated in Villin -Cre+ Lsd1 f/f mice 39 . However, upon performing intracellular flow cytometry staining for the canonical tuft cell marker DCLK1, we found that also a DCLK1 hi population fell within this gate and is increased in Lsd1 -deficient crypts ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…4b ). This supports our recent work in which we found that Lysine-specific Demethylase 1A (LSD1, KDM1A) is required for Paneth cell differentiation and contributes to goblet cell differentiation 39,40 . Paneth cells are commonly gated as SSC hi CD24+ population in flow cytometry 26 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation